Cover Feature: Cross‐Coupling through Ag(I)/Ag(III) Redox Manifold (Chem. Eur. J. 62/2021). Issue 62 (22nd October 2021) - Demonti, Luca; Saffon‐Merceron, Nathalie; Mézailles, Nicolas; Nebra, Noel
Abstract : Landing to explore beneath the silvery reflection of the moon, the unusual air oxidation of silver was investigated, granting access to the homoleptic anion [Ag III (CF3 )4 ] − (1 ). The crew compartment of the Lunar Lander illustrates the structure of 1 mimicking the heraldic Occitan Cross, symbol of Occitania, where this work was developed. Compound 1 reacts with 1, 10‐phenanthroline leading to the organosilver(III) compound [(phen)Ag III (CF3 )3 ], which is depicted in the descent stage of the Lunar Lander. Upon addition of aryl boron derivatives and base, [(phen)Ag III (CF3 )3 ] undergoes aromatic trifluoromethylation. More information can be found in the Full Paper by N. Nebra et al. (DOI: 10.1002/chem.202102836 ). Graphic design by Mariachiara Nespoli and Michele Bonventre.